Work at the time of digital subordination (“it began with a click and ended through text message”) - Arrigo, Gianni (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The enormous growth in the rate of IT computing power, storage capacity, connectedness and software applications has broader impacts on jobs, skills, wages, and the nature of work itself. The barriers between workplace and personal activities become increasingly blurred, and the level of monitoring and surveillance becomes more invasive. Employees scramble to be, or to stay, connected. While the benefits of an increasingly connected workforce in a more complex, diverse and dynamic global workplace are promoted, the potential negative consequences of e-communication are less noticeable. This article looks in particular at the impact of the digitalisation and ondemand economy on the labour relationship, and how it changes the roles of employers, employees and organisation of work. Considering the consequences of New ICTs for working time, workplace relations, individual and organizational performance, occupational safety and health, and work-life balance, the author highlights the importance of extending some fundamental labour rights to those working in the digital economy, particularly platform workers. Keywords: Labour law; Labour standards; digital labour; gig economy; platform workers.